Subjecting Verses : Latin Love Elegy and the Emergence of the Real - Miller, Paul Allen, 1959- (Book collections on Project MUSE., 2004)
The elegy flared into existence, commanded the cultural stage for several decades, then went extinct. This book accounts for the swift rise and sudden decline of a genre whose life span was incredibly brief relative to its impact. Examining every major poet from Catullus to Ovid, Subjecting Verses presents the first comprehensive history of Latin erotic elegy since Georg Luck's. Paul Allen Miller weds close readings of the poetry with insights from theoreticians as diverse as Jameson, Foucault, Lacan, and Zizek. He asks two questions: what historical conditions were necessary to produce elegy, and what provoked its decline? Ultimately, he argues that elegiac poetry arose from a fundamental split in the nature of subjectivity that occurred in the late first century--a split symptomatic of the historical changes taking place at the time. --From publisher's description.